Fear of future workplace violence and sleep quality in Chinese clinical nurses: the mediating role of anxiety and depression - Ping-Zhen Lin; Xu Wang; Yong-Sen Lin; Lan-Lan Chen; Bi-Yu Wu (BMC Nursing)
Abstract Objectives This study aims to examine the associations among fear of future violence at workplace, anxiety, depression, and sleep quality among Chinese clinical nurses. Methods A cross-sectional survey was carried out between June 2023 to July 2023 among Chinese clinical nurses who met the inclusion criteria. Data was collected using a structured questionnaire that included sociodemographic characteristics, fear of future violence at workplace (FFVW), Pittsburgh Sleep Quality Index (PSQI), Generalized Anxiety Disorder-7 (GAD-7), and Patient Health Questionnaire-9 (PHQ-9). Data of sociodemographics, FFVW, sleep quality, anxiety, and depression were analyzed by parallel and serial mediation models to evaluate the impact of anxiety and depression on the relationship between FFVW and sleep quality. Results A negative correlation between FFVW and sleep quality was observed (r = 0.300, P < 0.01). Parallel mediation analysis showed that anxiety and depression significantly mediated the association between FFVW and poor sleep quality (β = 0.069, 95% CI [0.024, 0.113]; β = 0.091, 95% CI [0.047, 0.135]), accounting for 52.29% of the total effect. Serial mediation analyses further confirmed bidirectional pathways involving anxiety and depression in mediating the effect of FFVW on poor sleep quality (β = 0.078, 95% CI [0.041, 0.120]; β = 0.057, 95% CI [0.019, 0.098]), which explained 25.50% and 18.63% of the total effect, respectively. Conclusions These findings contribute towards a more comprehensive understanding of the manner in which FFVW, anxiety, and depression jointly affect sleep quality among clinical nurses. This study provides novel insights for preventing and intervening in poor sleep quality by identifying FFVW reduction as a critical target, with anxiety and depression serving as modifiable mediating pathways. Clinical trial number Not applicable.